Isolation of Bacteria and Detection of Cephalosporin Antibiotics Effects among Patients with UTI in al-hilla City - Rawaa M. Mohammed; Asma’a HM (Indian Journal of Forensic Medicine & Toxicology, 2021)
90 urine samples were collected randomly from patients whose visit the Urology department in MurjanMedical City in Al-Hilla in period between April to July 2020 , the patients included 35 males and 55females and in age between 17-77 years old. The urine samples divided into two parts , the first part using forgeneral urine examination and the second part using for culture and sensitivity . The results of current studyappeared to 35 (39%) males among total patients infected with UTI while 55(61%) females among totalpatients infected with UTI . In field of effects of age on infection the current results appeared in females theinfection of urinary tract increase in young age group (17-27 years) in percentage (33%) in comparison withother age groups (20 %) in (27-37 years) , (16%) in (37-47 years) , (14%) in ( 47-57 years) , (10%) in (57-67years) and (7%) in (67-77 years) and in males the results appeared increase the UTI with age , (67-77 years)in percentage (32%) in comparison with other age groups, (3%) in (17-27 years) , (9%) in (27-37 years), (11%) in (37-47 years) , (20%) in ( 47-57 years) , (25%) in (57-67 years) . the results of API20 test thatusing for identification of types of bacteria which cause UTI appeared to 34 isolates of E.coli , 15 isolates ofEnterobacter spp. , 18 isolates of Klebsiella spp. , 11 isolates of Pseudomonas spp. , 13 isolates of S.aureusand 4 isolates of Acinetobacter spp. bacteria .In field of antibiotic sensitivity the results appeared the effectsof third and fourth generations of cephalosporin more than other generations .